Operation of single-phase direct AC-AC converter using single phase matrix converter / Zahirrudin Idris - Idris, Zahirrudin (2008)
In these work basic investigations are carried out on the operation of a proposed single-phase direct AC-AC converter using single phase matrix converter (SPMC) topology without the use of a DC-link. Three different categories of operation, namely; a) AC-AC converter, b) frequency changer (increased frequency) and c) decreased frequency (cycloconverter) are performed. The power circuit uses a common emitter mode with a pair of back-to-back IGBT with diode in series to realize its required bi-directional operation. A new safe commutation technique is proposed that uses simple switching scheme to avoid generation of damaging voltage spikes. Open-loop control was realised using the Sinusoidal Pulse Width Modulation (SPWM) implemented using digital techniques with Xilinx FPGA at the heart of its control electronics. Basic loads are used during operation to ascertain the behaviour. Prior to its practical realization a computer simulation model is developed to investigate the behaviour of the SPMC using Matlab/Simulink (MLS) incorporating SimPowerSystem and Pspice circuit simulation. An experimental test-rig was then constructed to verify the operation; incorporated with digital control, gate drives and power circuits. It will be presented that the proposed direct AC-AC converter using SPMC had been theoretically developed, conceived and successfully realized complete with safe commutation strategies.